Synoptic conditions of advection of arctic and tropical air masses over the Lublin region - Kaszewski, Bogusław Michał; Bartoszek, Krzysztof; Gluza, Andrzej (Annales Universitatis Mariae Curie-Sklodowska, sectio B – Geographia, Geologia, Mineralogia et Petrographia, 2018)
The aim of the study is to characterize the frequency and determinants of the synoptic conditions of advection of arctic and tropical air masses over the Lublin region. Their occurrence in the regional scale in the years 1951–2010 was based on lower synoptic maps for 12 UTC, which derived from PIHM/IMGW-PIB. In turn, the calendar of circulation types for the Lublin region was used to assess the synoptic conditions of the analyzed air masses. The annual frequency of arctic air masses reached 13.4%. The highest frequency of these air masses occurred in spring, with the maximum in April (20.4%), and the lowest in summer (July and August, < 5%). Days with tropical air were recorded less frequently (4.1% of all days in the year). It is most often found in the summer (with a maximum of 9.2% in July) and the lowest in winter (< 1%). In the years 1951–2010, there were signifi cant changes in the frequency of advection of arctic and tropical air masses (average increase by 8 and 3 days per 10 years, respectively). The occurrence of arctic masses signifi cantly increased in winter, autumn and spring, and tropical in the summer. In all seasons, the arctic air was most likely to be recorded during the northern and northeastern circulation types, while the lowest in the southern and southwestern types. In the case of tropical air, it is most likely to occur during air fl ow from directions E-SE-S-SW. Regardless of the time of the year, arctic and tropic air masses are characterized by signifi cant anomalies in air temperature at 850 hPa and 850–1000 hPa thickness. Celem opracowania jest charakterystyka częstości i uwarunkowań synoptycznych napływu mas powietrza arktycznego i zwrotnikowego nad obszar Lubelszczyzny. Ich występowanie w ujęciu regionalnym określono dla godziny 12 UTC na podstawie dolnych map synoptycznych PIHM/IMGW z okresu 1951-2010. Do oceny uwarunkowań synoptycznych napływu analizowanych mas powietrza wykorzystano kalendarz typów cyrkulacji dla Lubelszczyzny. Częstość napływu mas powietrza arktycznego w ciągu roku wynosiła 13,4%. Największy udział tych mas występuje wiosną, z maksimum w kwietniu (20,4%), najmniejszy zaś latem (w lipcu i sierpniu poniżej 5%). Rzadziej notuje się napływ powietrza zwrotnikowego (4,1% wszystkich dni w roku). Najczęściej nad Lubelszczyzną występuje ono w lecie (z maksimum w lipcu – 9,2%), natomiast najrzadziej w zimie (< 1%). W latach 1951-2010 zaznaczyły się istotne zmiany w częstości napływu nad Lubelszczyznę mas arktycznych (wzrost średnio o 8 dni na 10 lat) i zwrotnikowych (wzrost o blisko 3 dni na 10 lat). Udział mas arktycznych zwiększył się w zimie, jesieni i na wiosnę, mas zwrotnikowych zaś w lecie. We wszystkich porach roku największe prawdopodobieństwo występowania powietrza arktycznego notowano podczas typów cyrkulacji ze składową północną i północno-wschodnią, najmniejsze zaś w typach warunkujących adwekcję powietrza z południa i południo-zachodu. W przypadku powietrza zwrotnikowego największe prawdopodobieństwo jego wystąpienia notuje się podczas napływu powietrza z kierunków E-SE-S-SW. Niezależnie od pory roku, podczas występowania powietrza arktycznego i zwrotnikowego wykazano występowanie wyraźnych anomalii, zarówno temperatury powietrza na powierzchni izobarycznej 850 hPa, jak i średniej grubości warstwy powietrza między powierzchnią izobaryczną 850 i 1000 hPa.